Enterprise Creation in Agribusiness: An Analytical Estimation from a Score of Socio-Ecological Variables (Indian Journal of Extension Education, 2013)
Enterprise ecology manifests the complex interactions amongst a series of entrepreneurial functions. While enterprise management is a complex and challenging process, enterprise creation has been the most significant of a plethora of factors of entrepreneurships. In the transforming Indian agriculture, which is taking a shape and text of agripreneurship, the study of multilayer enterprise generation process unveils a new pathway for enterprise research. The present paper studies the enterprise creation, a conjugate dependent variable, in terms of a score of socio-ecological variables. The variables, market interaction, group interaction and planning orientation have been found to exert decisive impact on enterprise creation at the micro levels. The variables were subjected to factor analysis to group them into different factors, which would offer a strategic intervention for enterprise creation in given social ecology.